Nonlinear features of the transition of a liquid crystalline mixture into an isotropic state under the action of alcohol vapors - Mykytyuk, Z.; Barylo, H.; Kremer, I.; Kachurak, Y.; Samoilov, O.; Kogut, I. (Physics and Chemistry of Solid State, 2023)
The work of an optical sensor for determining the concentration of alcohols, in particular methanol, ethanol and isopropanol, based on a liquid crystal sensitive element, was studied. The sensitive element is a mixture of cholesteric liquid crystal CB15 and nematic impurity E7. The detection and reaction of the sensitive element to the presence of alcohol vapors is investigated.